The Profile of Classroom Action Research Skills Among Teachers in Indonesia: What is it Like and What Needs to be Done? - Dindin Nasrudin; Chaerul Rochman; Yudi Dirgantara; Anda Juanda; Fadilah Ilahi (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2024)
Research skills are crucial for modern teachers to identify and solve learning problems in their classrooms effectively. This study aims to profile teachers' research skills in Indonesia, underscore their importance in today's educational landscape, and propose policy options for enhancement. Using a survey method, questionnaires were distributed to 50 participants selected through purposive sampling to ensure a diverse representation in fields of study, gender, teaching experience, and employment status. This diversity provides a comprehensive understanding of teachers' research skills across various educational contexts. The analysis of the questionnaires was supplemented by in-depth interviews with a selected subset of respondents using a semi-structured format. Quantitative and qualitative methods provided a broad and detailed understanding of teachers' research skills. Content analysis was employed to identify themes and patterns in respondents' experiences. The results indicate that 9% of teachers are at the beginning stage (level 1), 38% need improvement (level 2), 43% are confident (level 3), and only 4% possess strong skills (level 4). Male teachers predominantly exhibit skills at levels 3 and 4, while female teachers are primarily at levels 2 and 3. The study concludes that there is significant variability in teachers' research skills, highlighting the need for targeted professional development programs. Recommendations include extensive training in research methodologies, data analysis techniques, academic writing, mentoring from supervisors, professional development instructors, and research collaborations with university lecturers to enhance teachers' research competence.